Pengaruh Konseling NLP (Neuro Linguistic Programming) Terhadap Tingkat Kecemasan Mahasiswa Kebidanan Selama Praktik Klinik - Setyaningsih, Dewi; Lestariningsih; Nugroho, Setyo Mahanani (STIKES Ngesti Waluyo, 2024)
Anxiety is an early symptom of students, which can have a negative impact on student achievement and learning outcomes. If the condition of anxiety is not treated, it can affect reducing immunity, depression, and reducing the quality of education. One approach that can be used is the Neuro-Linguistic Programming (NLP) method. Objective: To determine the effect of NLP techniques in reducing student anxiety during clinical practice. Method: Quantitative research using the Quasi-Experimental method using pre-test and post-test without control. This research used a total sampling of 33 students. Results: There was an effect of NLP therapy on students' anxiety levels while participating in Midwifery Clinical Practice with a p-value of 0.00 < 0.05.